Training recommendations specific to karate based on general motor and karate specific motor fitness differences and performance predictors for elite and novice karate athletes. - Keshishian, H.; Heazlewood, I. (Journal of Australian Strength and Conditioning, 2017)
Minimal research on general motor fitness tests of strength, power, speed, flexibility or karate specific motor fitness to assess differences between elite and novice karate athletes. Limited research on different interventions as kumite versus kata on anaerobic and aerobic responses and karate training improving balance. Specific karate skills as punch power, punch movement time and punch reaction time in terms of factors predicting performance have been rarely evaluated. Research aim integrated approaches of multivariate classification and multiple regression to evaluate motor fitness, both specific to karate and general to differentiate karate ability, as well as to identify motor factors predicting karate specific skill as reverse punch performance.